GESETZ UND PERVERSION ALS GRENZVERHÄLTNIS DES GENIESSENS. ZUR FRAGE DER ‟JOUISSANCE” IN PSYCHOANALYSE UND PHÄNOMENOLOGIE - KÜHN, Rolf (Studia Universitatis Babeș-Bolyai Philosophia, 2020)
Law and Perversion as the Limit of Enjoyment. On the Question of Jouissance in Psychoanalysis and Phenomenology. As a psychoanalyst, Jacques Lacan differentiated between the impossibility of symbolic representation covering the real (le réel) and the enjoyment (jouissance), which only partially subject itself to such signifiers and therefore leaves a real rest - the object a. This object a, which is different from the imaginary object, represents a non-assimilable excess that occurs on the one hand as the cause of desire (désir) and on the other hand refers back to the intrinsically concealed presence of object a as the origin of fear. The cure consists in crossing this phantasm to give up the original identification; that is, to see the tension between the desire for recognition and the demand in need (besoin) and thereby to dissolve it. Insofar as the subject is split between the singular truth of desire and a general knowledge about it, interdiction, law and perversion are forming a special relation as frontier of enjoyment.